Sex-Specific Differences in Peripheral Nerve Properties: A Comparative Analysis of Conduction Velocity and Cross-Sectional Area in Upper and Lower Limbs - Ayaka Nobue; Masaki Ishikawa (Diagnostics)
Background/Objectives: Peripheral nerve conduction velocity (NCV) and nerve cross-sectional area (nCSA) are crucial parameters in neurophysiological assessments, yet their sex-specific differences are not fully understood. This study investigated sex-based variations in NCV and nCSA between upper and lower limbs. Methods: Twenty participants (ten males and ten females) were recruited for this study. The NCV and nCSA of the ulnar and tibial nerves were measured in both the upper and lower limbs. NCV was measured using supramaximal electric stimulation, and nCSA was assessed using peripheral nerve ultrasonography at three regions for each nerve. Supramaximal electric stimulations were applied superficially to the ulnar and tibial nerves at each measurement point. Action potentials were recorded from the abductor digiti minimi and soleus muscles for the ulnar and tibial nerves, respectively. Results: The ulnar nCSA of the upper limbs was significantly greater in males than in females (p < 0.05). However, ulnar NCV was significantly higher in females than in males (p < 0.05). In the lower limbs, no sex differences were observed in tibial NCV or nCSA. Conclusions: These findings reveal sex-specific differences in upper limb peripheral nerve characteristics that may have important implications for clinical assessments and treatment strategies. The contrasting patterns between upper and lower limbs suggest that both developmental and functional factors influence peripheral nerve properties.